A Production and operations management study on Star Paper Corporation - Endaya, Victor Carlo (College of Engineering, 1999)
This study focuses on the production and operations of the factory of Star paper Corp. at 46 Joy St, Grace Village, Quezon City. The primary objective of the study is to provide recommendations to improve the operations of the said company. The study was conducted from December to March 1999. The operations of the factory was documented through observation and interviews with key personnel and evaluated using production and operations management tools. Analysis of the current system shows that the company does not have a standard scheduling procedure. Due to this lack of efficient scheduling the factory's machines are sometimes over-utilized and sometimes under-utilized. The inventory levels are also affected by the lack of a standard scheduling procedure. Further analysis shows that poor scheduling is affected by two problems of Star Paper which is undetermined capacity and decentralized forecasting among product managers. The study provided solutions to the problems by determining the company's capacity and recommending an adequate forecasting method. The provided solutions can readily be used by the company for its decision making. Furthermore, these solutions were used to support a recommended scheduling procedure. The scheduling procedure may be used by the company to better control the utilization of its factory. Over-utilization and under-utilization will be better controlled. The use of overtime capacity of the factory can be predicted since the capacity is already known. This will reduce production costs. It will also follow that the inventory levels would be improved since products are produced what is needed when its needed. The company can readily apply the recommendations presented since it involves little capital expenditure.